Exergy analysis and energy improvement of a Brazilian floating oil platform using Organic Rankine Cycles. (August 2015) - Barrera, Julian Esteban; Bazzo, Edson; Kami, Eduardo
Abstract: This paper focuses on the exergy performance analysis of the processes on board of a Brazilian FPSO (Floating Production, Storage and Offloading unit) and the integration of an ORC (Organic Rankine Cycle) for improving its efficiency. Based on the exergy analysis of the plant, the integration of an ORC to the existing heat recovery system was modeled. Cyclopentane was chosen as the working fluid and the best configuration of the cycle was determined according to its vapor saturation curve. The improvement was quantified using the plant exergy efficiency and an energy-consumption indicator, assuming a distributed part-load operation of two gas turbines. The study was carried out along an arbitrary profile, at which five of the main production parameters were analyzed separately. According to the results, it appears that the ORC integration has a great potential for generating useful work from the exergy of the exhaust gases, representing savings along the production profile of about 15% based on fuel consumption. On the other hand, the overall exergy efficiency and the ORC power output are strongly influenced by the amounts of gas and water injected back to the reservoir. Highlights: Modelling of a typical floating platform is developed accounting exergy flows. Scarcity of data and algorithm integration with commercial simulators are considered. Exergy efficiency formulation seems to be adequate for this type of installations. Impact of an Organic Rankine Cycle over the plant exergy performance is analyzed. Injection processes are the most influencing parameters over the plant efficiency.